Statistical process control and strength monitoring of ready-mixed concrete through the application of CUSUM and EWMA control charts: a case study of Ahmedabad and Gandhinagar RMC plants. (10th January 2019) - Gohel, Jishnu; Sarkar, Debasis; Raghavendra, H.B.
This research work is an attempt to improve the quality of concrete by implementing statistical process control tools like CUSUM with V-mask and exponentially weighted moving average (EWMA) control charts for ready-mixed concrete (RMC) plants in the Gandhinagar and Ahmedabad regions of India. These tools are used for sensitising the qualitative analysis of concrete in terms of the 28 days cube compressive strength. It has been observed that the RMC plant authorities were using an over-conservative mix design for the grades of concrete produced. This practice resulted in the usage of more cement than that stipulated in the mix design. The usage of higher cement content is wastage of resource. Also, this practice results in adverse side effects like production of more heat of hydration which creates shrinkage cracks. The application of these tools for strength monitoring would result in cost savings of about INR 4.8 million to 7.2 million per annum.